Placement of dental implants in the maxillary tuberosity: a systematic review - Lopes, L. F. dT. P. [UNESP]; Silva, V. F. da [UNESP]; Santiago, J. F. [UNESP]; Baarioni, Sonia Regina Panzarini [UNESP]; Pellizzer, Eduardo Piza [UNESP] (Churchill Livingstone, 2015)
The aim of this systematic review was to identify clinical studies on implants placed in the tuberosity region to determine the survival rate of these implants when compared to implants placed in other regions of the maxilla. A search for data published up until March 2014 was undertaken using the PubMed, Cochrane Library, Embase, and ScienceDirect databases. Eligible studies were selected according to inclusion and exclusion criteria. The first database search revealed 310 titles. After inclusion and exclusion criteria were applied, five studies remained for the detailed analysis. A total of 113 patients were followed for a period of 6-144 months; 289 implants were placed in the patients evaluated. There were eight failures/losses of dental implants in the tuberosity region; the overall survival rate was 94.63% for these implants. In controlled studies, the cumulative survival rates for implants placed in the maxillary tuberosity and other maxillary regions were 96.1% and 95%, respectively. In conclusion, implants placed into the maxillary tuberosity are a predictable alternative for the treatment of patients with insufficient bone volume in the maxillary region. However, randomized trials are needed to assess the effectiveness of this treatment.
Keywords: dental implants; maxilla; maxillary sinus; alveolar bone